Okun's law, Phillips curve and its effect on the growth of Income Tax Article 21 payments during Covid-19 pandemic - Galih Ardin (Directorate General of Taxes, 2023)
The Covid-19 pandemic has changed the macroeconomics indicators not only in Indonesia but also in other countries in the world. Restrictions on social activities, lockdowns, a decline in aggregate demand and supply as well as a drop in export and import activities have triggered a decrease in economic growth, increase unemployment rate, and stagnation of inflation rates leading to deflation. Logically, the turmoil in macroeconomic indicators will affect tax revenues, especially Article 21 Income Tax. Through the Okun’s law and Phillips curve approach, this research tries to examine the relationship between unemployment rates, economic growth, and inflation rates during the pandemic on income tax payments Article 21. Based on the examination using the Ordinary Least Squares (OLS) method, it founds that the unemployment rate does not have a significant effect on economic growth and inflation rates in Indonesia. In addition, economic growth also does not affect the payment of Income Tax Article 21. However, there is an interesting finding where the inflation rate has a positive effect on the payment of Income Tax Article 21 in Indonesia.